GE_GERICHTE P/9985/2016 vom 23. Mai 2018 - GE Cour de justice (2018)
ESCROQUERIE ; FAUX DANS LES CERTIFICATS ; CONCURRENCE DÉLOYALE ; ANNONCE INSÉRÉE DANS LA PRESSE | CP.251; CP.146; CP.2.al2; CP.a42.al1; CP.44.al1; CP.49.al1; LCD.23; LCD.3.al1.letb; LCD.3.al1.letd